Implementasi Pendidikan Quran Tingkat Lanjut Bagi Santri Usia Dewasa - Supriati H. Rahayu; Hidayatul Huda; Joko Wahono; Difla Nadjih; A. Zain Sarnoto (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2019)
The researchers intends to find out how Al-Quran Education in the Yogyakarta AMM Tartil Team includes supporting and inhibiting factors as well as how the team overcomes the obstacles to Al-Quran Education in the AMM Tartil Team Yogyakarta. The learning patterns of adults and advanced readers of the Quran in this education are different from those of students of Quran who are younger than them at the beginning level or those studying in Islamic boarding schools. This qualitative case study research uses several instruments, observation, mandala interviews, and documentation. Observations were made by directly following the Syahadah One education process for the students of the AMM Yogyakarta tartil team. In-depth interviews were addressed to informants, namely the management of the Foundation, Ustaz, and students participating in the education who were the object of the research. For documentation, it is emphasized on the data of the Tartilil Qur'an curriculum text. All collected data were then analyzed in a cumulative manner with inductive-deductive thinking patterns. Advanced education to read the Koran does have complex problems in terms of time and age of the participants, although it must be commended for their intention and sincerity to be fluent in reading it.